RESPONS PERTUMBUHAN BIBIT PULAI (Alstonia scholaris) TERHADAP CUKA KAYU DAN NAUNGAN - Mery, Feronika; Ekamawanti, Hanna Artuti; Astiani, Dwi (JURNAL HUTAN LESTARI, 2019)
Pulai (Alstonia scholaris) is a fast growing local species that can be used rehabilitation activities on peat swamp forest. This study aims to obtain information application the response of growth and quality of pulai seedlings to wood vinegar and shade. The research was carried out at orchid exsitu observation site stockÂ  and community service and in the silvicultural laboratory of Faculty of Forestry. This study applied an experimental method with a split plot design with a complete randomized design (CRD). The treatment consisted of two factors,â€œshadingâ€ as the main factor and kind ofÂ  organic vinegar as Â sub Â factor. The results obtained were based on observations 12 weeks after planting, the growth percentage of pulai seedlings for the 100%, while ofthen variables in this study had no effect. The main factor is organic fertilizer with 2 levels: chemical fertilizer and wood vinegar, while the shade factor is a main factor that less interest. Results showed that the response of height growth was significantly higher 13.0% to chemical fertilizer than wood vinegar when planted in a shadeless condition. However, if planted in conditions with a shade of 60%, the response was no different. The response of leaves growth to fertilizer is significant when planted under different shade conditions. In the condition without shade, the response of leaves is 11.8% higher compared to wood vinegar. Conversely, in condition with shading 60%, the response Â the number of leaves growth on wood vinegar was 13.0% higher than that of chemical fertilizer. In this study, the concentration of wood vinegar as much as 4% was not effective enough to increase the enhance Â of pulai seedlings.Keywoards: Organic vinegar, pulai seedlings, shade